DOI: 10.31274/rtd-180813-10798
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ionizing radiation on pork, beef, and turkey quality

Abstract: This manuscript has been reproduced from the microfilm master. UMI films the text directly from the original or copy submitted. Thus, some thesis and dissertation copies are in typewriter face, while others may be from any type of computer printer.The quality of this reproduction is dependent upon the quality of the copy submitted. Broken or indistinct print, colored or poor quality illustrations and photographs, print bleedthrough, substandard margins, and improper alignment can adversely affect reproduction.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
(86 reference statements)
1
5
0
Order By: Relevance
“… Nam and Ahn (2003) reported that a* values of short term-aged beef were not changed much during storage and the redness was higher in nonirradiated than irradiated beef. This result agrees with many authors who reported that vacuum-packaged irradiated beef reduced a* and b* values during storage ( Ahn and Nam, 2004 ; Nam and Ahn, 2003 ; Nanke, 1998 ). Reflectance data indicated that both O 2 -Mb and Fe 3+ -Mb developed but a significant decrease in red and increase in brown pigments could develop at dose levels as low as 1.5 kGy in vacuum-packaged beef ( Brewer, 2004 ).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“… Nam and Ahn (2003) reported that a* values of short term-aged beef were not changed much during storage and the redness was higher in nonirradiated than irradiated beef. This result agrees with many authors who reported that vacuum-packaged irradiated beef reduced a* and b* values during storage ( Ahn and Nam, 2004 ; Nam and Ahn, 2003 ; Nanke, 1998 ). Reflectance data indicated that both O 2 -Mb and Fe 3+ -Mb developed but a significant decrease in red and increase in brown pigments could develop at dose levels as low as 1.5 kGy in vacuum-packaged beef ( Brewer, 2004 ).…”
Section: Resultssupporting
confidence: 93%
“…(1997) reported that irradiation at 2.0 and 3.5 kGy initially darkened and reduced the redness of raw beef patties in aerobic or vacuum packaging, but the color difference disappeared with display time. Nanke (1998) suggested that color changes of irradiated raw meat were species, irradiation dose, and packaging type dependent.…”
Section: Resultsmentioning
confidence: 99%
“…(1997) reported that irradiation at 2.0 and 3.5 kGy initially reduced the redness of raw beef patties in aerobic or vacuum packaging, but the color difference disappeared with display time. Nanke (1998) suggested that color changes of irradiated raw meat were dependent on species, irradiation dose, and packaging type.…”
Section: Resultsmentioning
confidence: 99%
“…They found significant decrease in L* in fresh irradiated beef and after storage of 14 days, as well as decrease in Food Science and Applied Biotechnology, 2022, 5(2), 160-172 a* and b* values throughout the whole storage period after irradiation. Nanke (1998), demonstrated that irradiation induced OxyMb pigment in vacuum packaged pork, whereas in beef it led to formation of both Oxy-and MetMb like pigments. Furthermore, it was shown that colour changes appeared to be independent of myoglobin concentration.…”
Section: Effect Of Gamma Irradiation On the Colour Of Chicken Meatmentioning
confidence: 99%